Endocytosis in the retinal and choroidal microcirculation. - Gardiner, T A (1986)
The endocytosis of horseradish peroxidase (HRP) by the vascular cells of retinal and choroidal blood vessels was compared in immersion and perfusion fixed eyes from individual rats. The mechanisms of endocytosis of HRP appeared identical in both retinal and choroidal vessels. The bulk of internalised tracer occurred in macropinosomes 300-400 nm in diameter. Tracer was localised to a 20-30 nm layer on the internal aspect of the limiting membrane. This layer was coincident with the glycocalyx of the luminal plasma membrane as revealed by ruthenium redosmium tetroxide staining. Horseradish peroxidase was also internalised by a small scattered population of vesicles (100-130 nm in diameter). The size of these vesicles suggested that they may have arisen from clathrin coated regions of the plasma membrane. It is suggested that the endocytosis of HRP in retinal and choroidal vascular endothelium occurs as a function of plasma membrane recycling. Horseradish peroxidase may also be internalised as a 'contaminant' of the glycocalyx in coated pits involved in receptor mediated endocytosis. The smooth 80 nm plasmalemmal caveolae of the retinal and choroidal vascular endothelial cells did not appear to participate either in absorptive endocytosis or vesicular transport.